Studies of Synthesis and Antibacterial Activity of Chalkones and Flavones. - SUBBANWAD, G.R.; DASHARATH, D.; VIBHUTE, Y.B. (Asian Journal of Chemistry, 2010)
Two new chalkones and two new flavones have been synthesized and tested for their antibacterial activity.